2005
DOI: 10.4161/cc.4.10.2086
|View full text |Cite
|
Sign up to set email alerts
|

AEC-Associated p63 Mutations Lead to Alternative Splicing/Protein Stabilization of p63 and Modulation of Notch Signaling

Abstract: ABSTRACTp63, the major regulator of epithelial development/differentiation, is mutated in human ectodermal dysplasias, such as ankyloblepharon, ectodermal dysplasia and clefting (AEC). We recently identified that p63α physically associated with mRNA processing/ splicing proteins. We previously showed that p63 mutations mapped to the sterile α-motif led to disruption of these interactions and modulated an aberrant splicing of keratinocyte growth factor receptor contributing into molecular mechanism underlying A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Mutations within the SAM domain responsible for AEC syndrome were originally described as inhibiting the transactivation of a p53 consensus promoter by TAp63, while also abolishing the ability of the Np63 isoform to inhibit p53-or TAp63-mediated transactivation (McGrath et al, 2001). The L514F (leucine 514 to phenylalanine) mutation within the SAM domain has been demonstrated to impair the ability of Np63 to bind and inhibit the splicing factors apobec-1-binding protein-1 (ABBP1) and SRA4, leading to aberrant spicing of components of the FGF and Notch signalling pathways and, indeed, of p63 itself (Candi et al, 2007b;Fomenkov et al, 2003;Huang et al, 2005). Mutations within the SAM domain of p63 have also been reported to prevent its direct binding and transcriptional regulation of the cell cycle checkpoint protein stratifin/14-3-3 (Fomenkov et al, 2003;Westfall et al, 2003).…”
mentioning
confidence: 99%
“…Mutations within the SAM domain responsible for AEC syndrome were originally described as inhibiting the transactivation of a p53 consensus promoter by TAp63, while also abolishing the ability of the Np63 isoform to inhibit p53-or TAp63-mediated transactivation (McGrath et al, 2001). The L514F (leucine 514 to phenylalanine) mutation within the SAM domain has been demonstrated to impair the ability of Np63 to bind and inhibit the splicing factors apobec-1-binding protein-1 (ABBP1) and SRA4, leading to aberrant spicing of components of the FGF and Notch signalling pathways and, indeed, of p63 itself (Candi et al, 2007b;Fomenkov et al, 2003;Huang et al, 2005). Mutations within the SAM domain of p63 have also been reported to prevent its direct binding and transcriptional regulation of the cell cycle checkpoint protein stratifin/14-3-3 (Fomenkov et al, 2003;Westfall et al, 2003).…”
mentioning
confidence: 99%
“…Among these mRNA targets, we found RPN13 (also known ADRM1). We previously showed that cisplatin treatment induces the ATM-dependent phosphorylation of ⌬Np63␣, subsequently modulating various genes implicated in cell survival (33,(35)(36)(37). Using the isogenic HNSCC cell lines expressing wild-type ⌬Np63␣ or ⌬Np63␣-S385G (⌬Np63␣ with an altered ability to be phosphorylated by ATM kinase), we previously showed the failure of ⌬Np63␣-S385G to regulate gene transcription (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Cells and Reagents-We used HNSCC stable cell lines expressing wild-type ⌬Np63␣ or ⌬Np63␣-S385G (with an altered ability to be phosphorylated by ATM kinase) as described previously (33,(35)(36)(37). Cells were maintained in RPMI 1640 medium and 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations